The Role of Cultural Aspect of Pesarean on the Regulation Formation in Wonosari Village of Gunung Kawi - Jazim Hamidi; M Gatot Subratayuda; M Fajrul Falah (Fakultas Hukum, Universitas Warmadewa, 2018)
This article discusses how the role of cultural aspects influences the formation of regulation in Wonosari Village Gunung Kawi, Malang Regency. In accordance with the issues raised, this study uses empirical juridical method and the theory of legal harmonization and legal pluralism as a tool for analysis. The conclusions of this research are; (1) Culture has an important role in the formation of law. Culture makes the law work well in the community. (2) The Pesarean region of Gunung Kawi is currently undergoing a transformation from traditional values ​​to modern values. (3) Therefore the urgency now is to create harmonization and unification between culture and formal law. Furthermore the authors advise the government to always consider cultural values ​​in the framework of the formation of village regulations.